2020
DOI: 10.1016/j.jse.2019.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty with and without latissimus and teres major transfer for patients with combined loss of elevation and external rotation: a prospective, randomized investigation

Abstract: Background: Latissimus dorsi (LD) and teres major (TM) tendon transfers have been performed concurrently with reverse shoulder arthroplasty (RSA) to address combined loss of elevation and external rotation (CLEER) at the shoulder. The purpose of this prospective, randomized study was to compare RSA with and without LD-TM tendon transfer in patients with rotator cuff tear arthropathy and CLEER. Methods: Patients undergoing RSA for rotator cuff tear arthropathy who also had CLEER were randomized into the group u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 27 publications
1
26
1
1
Order By: Relevance
“…Effectively, it has traditionally been implied for this condition that a latissimus dorsi transfer +/− teres major tendon transfer(s) be undertaken [31,32]. Our study demonstrated that an adequate prosthetic design could be sufficient to restore active external rotation, confirming other reports [33]. Consequently, due to the additional difficulty, increased operative time, associated loss of internal rotation [34], and increased neurological complication rate [35], primary transfers do no longer seem justified, as a simple change in prosthetic design could achieve similar results.…”
Section: Discussionsupporting
confidence: 87%
“…Effectively, it has traditionally been implied for this condition that a latissimus dorsi transfer +/− teres major tendon transfer(s) be undertaken [31,32]. Our study demonstrated that an adequate prosthetic design could be sufficient to restore active external rotation, confirming other reports [33]. Consequently, due to the additional difficulty, increased operative time, associated loss of internal rotation [34], and increased neurological complication rate [35], primary transfers do no longer seem justified, as a simple change in prosthetic design could achieve similar results.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, Young et al reported that there were no significant differences in ADLER, DASH, ASES, and SST scores for patients treated with RTSA alone or if the LDT was done concomitantly with RTSA. 15 This was done in a series of patients presenting with rotator cuff arthropathy and loss of range of motion. However, little data are available for patients presenting with other indications such as hemiarthroplasty revision or failed ORIF.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report follow-up of less than five years. [12][13][14][15] The purpose of this article is to report mid-term outcomes of RTSA with LDT. We hypothesized that positive outcomes will demonstrate an increase in range of motion and a reduced pain level that is sustained.…”
Section: Introductionmentioning
confidence: 99%
“…This classification was developed after early observations of poorer outcomes of reverse shoulder arthroplasty (RSA) in combined pseudoparalytic syndromes especially with additional loss of ER ( 18 ). Treatment of CLEER is currently controversial, with some surgeons suggesting it should be treated with RSA combined with a simultaneous tendon transfer ( 17 , 19 , 20 ) and others suggesting that using a lateralized RSA prosthesis is adequate ( 21 , 22 ). It is the authors’ opinion and experience that there are patients who still suffer from loss of ER with a hornblower and dropping sign despite RSA lateralization ( Fig.…”
Section: Definitionmentioning
confidence: 99%